Dynamics and organization of cortical microtubules as revealed by superresolution structured illumination microscopy - Komis, George; Mistrik, Martin; Samajová, Olga; Doskočilová, Anna; Ovečka, Miroslav; Illés, Peter; Bartek, Jiri; Samaj, Jozef (Plant physiology, 2014)
Plants employ acentrosomal mechanisms to organize cortical microtubule arrays essential for cell growth and differentiation. Using structured illumination microscopy (SIM) adopted for the optimal documentation of Arabidopsis (Arabidopsis thaliana) hypocotyl epidermal cells, dynamic cortical microtubules labeled with green fluorescent protein fused to the microtubule-binding domain of the mammalian microtubule-associated protein MAP4 and with green fluorescent protein-fused to the alpha tubulin6 were comparatively recorded in wild-type Arabidopsis plants and in the mitogen-activated protein kinase mutant mpk4 possessing the former microtubule marker. The mpk4 mutant exhibits extensive microtubule bundling, due to increased abundance and reduced phosphorylation of the microtubule-associated protein MAP65-1, thus providing a very useful genetic tool to record intrabundle microtubule dynamics at the subdiffraction level. SIM imaging revealed nano-sized defects in microtubule bundling, spatially resolved microtubule branching and release, and finally allowed the quantification of individual microtubules within cortical bundles. Time-lapse SIM imaging allowed the visualization of subdiffraction, short-lived excursions of the microtubule plus end, and dynamic instability behavior of both ends during free, intrabundle, or microtubule-templated microtubule growth and shrinkage. Finally, short, rigid, and nondynamic microtubule bundles in the mpk4 mutant were observed to glide along the parent microtubule in a tip-wise manner. In conclusion, this study demonstrates the potential of SIM for superresolution time-lapse imaging of plant cells, showing unprecedented details accompanying microtubule dynamic organization.
Keywords: mutace; Green Fluorescent Proteins; Plant Epidermis; mikrotubuly; Arabidopsis Proteins; Recombinant Fusion Proteins; rekombinantní fúzní proteiny; Mutation; hypokotyl; proteiny huseníčku; Hypocotyl; osvětlení; zelené fluorescenční proteiny; Lighting; Microtubules; epidermis rostlin; Arabidopsis; Microscopy, Confocal; konfokální mikroskopie; mikroskopie; Microscopy